12 Pillars’ Framework for Successful Financial Inclusion in India - Viswanatha Reddy, C. (Indian Journal of Finance, 2016)
Financial inclusion has been accorded high importance by the GoI and RBI to aid the inclusive growth process of the economy, but the impact of these have not yielded agreeable results. There have been formidable challenges in this area such as bringing sections of society that are financially excluded within the ambit of the formal financial system, providing financial literacy, and strengthening credit delivery mechanisms. As the majority of the rural population is still not included in inclusive growth, the concept of financial inclusion is a challenge for the Indian economy. The present study made an attempt to study the effectiveness of the existing resources such as network of bank branches, business correspondents (BCs), basic savings bank deposit accounts with overdraft facility, financial literacy, and credit counselling, credit guarantee fund, micro insurance, unorganised sector pension schemes, payment banks, post offices, and fair price shops network, information technology, banking technologies, PMJDY, and MUDRA Yojana, etc., towards financial inclusion. The study found that there is a still lacuna which needs to be covered, thereby making financial inclusion more efficient and user-friendly for the financially untouchable rural population.